Current Practice Patterns and Opinions on the Management of Recent-Onset or Chronic Herpes Zoster Ophthalmicus of Zoster Eye Disease Study Investigators. Issue 1 (January 2019) - Lo, Danielle M.; Jeng, Bennie H.; Gillespie, Colleen; Wu, Mengfei; Cohen, Elisabeth J.
Abstract : Purpose: To determine practices and opinions among study investigators in the Zoster Eye Disease Study (ZEDS) regarding suppressive valacyclovir treatment for recent-onset and chronic herpes zoster ophthalmicus (HZO). Methods: An Internet-based survey was distributed to 170 ZEDS study investigators with questions regarding treatment practices for stromal keratitis in HZO and opinions regarding the efficacy of prolonged antiviral prophylaxis. Results: The response rate was 72.4% (123/170). Topical steroids and oral antivirals were used by the majority of respondents for stromal keratitis in both recent-onset (69.1%, 85/123) and chronic HZO (63.4%, 78/123) ( P = 0.86). The duration of treatment was similar in both recent-onset and chronic HZO ( P = 0.58) with 50.4% (124/246) of ZEDS investigators using prolonged treatment for stromal keratitis due to recent-onset or chronic HZO. The majority of ZEDS respondents believe that oral antivirals are effective during treatment (70.7%, 87/123). Conclusions: Approximately half of ZEDS investigators treat HZO with prolonged oral antivirals, in addition to topical steroids, and two-thirds believe that it is effective. Completion of ZEDS is feasible and necessary to determine whether or not these practices are effective. Participation in this study is necessary to obtain evidence to support treatment that many ophthalmologists use and believe is effective. Abstract : Supplemental Digital Content is Available in the Text.